Oxytetracycline is more suitable antibiotic for clinical endometritis cows - MANIMARAN, AYYASAMY; RAGHU, H V; KUMARESAN, A; SREELA, L; YADAV, ASHA; LAYEK, S S; MOOVENTHAN, P; CHAND, S; SARKAR, SOUVENDRA NATH; SIVARAM, M (The Indian Journal of Animal Sciences, 2019)
We identified the bacterial isolates from the uterus of clinical endometritis affected cows and performed in vitro antibiotic sensitivity test (ABST) against major uterine pathogen (E. coli). We subsequently evaluated the sensitive antibiotics in clinical endometritis affected cows through fertility parameters, blood acute phase proteins (APPs; haptoglobin and serum amyloid A), cytokines level (IL-1Î² and TNF-Î±) and milk yield. We found 12.7% of E. coli among 63 bacterial isolates from the endometritis cows. ABST against E. coli revealed gentamicin as the most sensitive and oxytetracycline (OTC) as intermediately sensitive drug. Minimum inhibitory concentration (Î¼g/ml) of gentamicin and OTC against E. coli was 5.47 and 0.78, respectively. Gentamicin, OTC, and povidone-iodine (PI) were administered for 3 days through intrauterine route in endometritis cows (8 per group) for in vivo evaluation. The first service conception rate was higher in OTC treated cows with lesser days open, while interval between treatment and conception was nonsignificantly lower in PI-treated cows. The concentration of APPs and cytokines was significantly reduced in antibiotics treated cows but not in PI-treated groups. In conclusion, OTC was found to be more suitable than gentamicin for treatment of clinical endometritis and PI had differential effects on clinical endometritis cows.